Measuring the Effectiveness of Differential Calculus Learning Using Open Ended Based Teaching Materials - Yurechko, Mariyan; Pryimak, Evgen (Research Collaboration Community (Rescollacom), 2022)
This study aims to produce differential calculus teaching materials using a good (valid, practical and effective) open-ended approach to improve students' critical and creative thinking skills, and compare their effectiveness with teaching materials prepared in the context of implementing the implemented curriculum. This research is research and development (Research and Development). The development models referred to are the modified Dick & Carey and Borg & Gall models. The steps in this development are researching and gathering information, developing teaching, selecting and developing teaching materials, initial trials, revisions, main trials, and final product revisions. Initial trials and main trials are carried out in a university. Product validity is validated by experts. Product practicality is assessed by product users, namely lecturers and students. Product effectiveness was tested using an inferential statistical test by looking at the significant differences in the mean of the pretest and posttest scores in terms of students' critical and creative thinking abilities. Next, the effectiveness will be compared between the control class and the experimental class. The results of the research show that the product developed is in the very valid category according to the experts, practical according to the teacher's assessment, and very practical according to the students. The resulting product is also effective, even more effective when compared to teaching materials in terms of critical and creative thinking skills student.